Numerical simulation on the stability of roadway surrounding rock in the end coal drawing area - GAO Peng; ZHAO Zhining; DU Houlin; PAN Weidong; ZHA Dashun (矿业科学学报)
To address the significant of top coal loss due to the absence of coal drawing at the end of fully mechanized top-coal caving faces, this study established a two-dimensional numerical model with the Yuandian No. 1 Mine of Huaibei Mining Group as an example for analysis. Specifically, we analyzed the dynamic variations and characteristics of the displacement field and force chain field of the coal-rock mass during the end coal drawing process. We proposed methods for safe coal drawing section division and precise coal drawing schemes. Additionally, we put forward a support modification scheme in response to the insufficient existing coal drawing space at the end. Results show that: ①The active support of the anchor (cable) in the roadway fails successively before the formal coal drawing at the end area, due to the influence of the coal drawing in the middle of the working face. However, there are temporal and spatial differences in the failure of the active support effect of the anchor (cable) at the upper and lower end roadways. ② The flow of the coal-rock mass demonstrate significant differences in at the upper and lower ends of the working face during the end coal drawing process. The coal-rock mass in the bearing structure around the lower end roadway gradually loosens with the increase in the number of transition supports, leading to a gradual weakening of bearing capacity. The coal-rock mass in the bearing structure around the upper end roadway experiences advanced loosening due to the influence of coal drawing in the middle of the working face, with the advanced influence distance being proportional to the dip angle of the working face. The coal-rock mass within the advanced influence range will also gradually loosen and eventually penetrate. ③The sectional range of the end coal drawing area has a significant impact on the bearing capacity of the surrounding roadway structure. To maintain the stability of the bearing structure, the end coal drawing scheme for the working face can be set as: overall partitioning at the lower end and segmented partitioning within the support at the upper end.